2023
DOI: 10.1080/0886022x.2023.2259996
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the application of the neutrophil-to-lymphocyte ratio in dialysis-related complications

Nan Yang,
Kaibi Yang,
Shujun Pan
et al.

Abstract: The neutrophil-to-lymphocyte ratio (NLR) is a novel predictive biomarker that reflects systemic inflammatory status and is routinely measured in blood tests. Owing to its ease of use and affordability, it is being increasing used as a prognostic indicator of cardiovascular disease, tumors, autoimmune disorders, and kidney disease. In recent years, a number of studies have demonstrated the clinical utility of the NLR in identifying and predicting complications associated with hemodialysis and peritoneal dialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Nan Yang et al. pointed out in their review that NLR has a good predictive ability for the complications in dialysis patients, including CVD and infection [ 24 ]. Previous research has shown that the Pan-immune-inflammation value (PIV) is also associated with all-cause death, CVD and infection in PD patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nan Yang et al. pointed out in their review that NLR has a good predictive ability for the complications in dialysis patients, including CVD and infection [ 24 ]. Previous research has shown that the Pan-immune-inflammation value (PIV) is also associated with all-cause death, CVD and infection in PD patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%